Metal and Metalloid Contamination in Green Sea Turtles (Chelonia mydas) Found Stranded in Southeastern Brazil - Bruno, Daphne de Albuquerque; Willmer, Isabel Q.; Pereira, Lucia Helena S. de S.; Rocha, Rafael C. C.; Saint’Pierre, Tatiana D.; Baldassin, Paula; Scarelli, Ana Carolina S.; Tadeu, Amanda Dias; Correia, Fábio V.; Saggioro, Enrico M.; Lemos, Leila S.; Siciliano, Salvatore; et al. (Frontiers in Marine Science, 2021)
Sea turtles tend to accumulate high metal levels in their tissues and are considered excellent pollution bioindicators. Studies concerning metal contamination in hatchlings, however, are non-existent for one of the most abundant species in Brazil, green sea turtles, while several other metal assessments in juvenile muscles are still scarce. In this context, this study aimed to analyze the concentrations of 12 elements in kidney and muscle samples from green sea turtles (Chelonia mydas; n = 24) found stranded in Rio de Janeiro, southeastern Brazil. Elemental concentrations were determined by inductively coupled plasma mass spectrometry (ICP-MS). The presence of fibropapillomatosis, an increasingly common disease in sea turtles which has been associated to metal contamination, was also evaluated. Most elements (Mn, Fe, Co, Ni, Cu, Zn, Cd, Hg, and Pb) were significantly higher in liver, while Al and As were significantly higher in muscle tissue, indicating bioaccumulation of the latter two elements. No differences between juvenile male and female green turtles were observed for either liver or kidney concerning the investigated elements. Literature comparisons of studies conducted in other areas throughout the Brazilian coast indicate higher concentrations of Cd, Mn, As, Hg, and Zn in kidneys, of probable anthropogenic origin. Several statistically significant inter-elemental correlations were observed between toxic elements, indicating similar sources for these environmental contaminants. Significant correlations between Hg in muscle and kidney and As in the same organs suggest bioaccumulation of both elements in muscle. Three individuals assessed herein exhibited fibropapillomatosis, and further assessments in this regard and potential correlations to the detected metal concentrations are currently being carried out. In addition, evaluations concerning other toxic compounds, as well as deleterious cellular effects, are also underway, since total metal concentrations do not reflect total elemental bioavailability.